Functional characterization of an oxytocin receptor gene variant (rs2268498) previously associated with social cognition by expression analysis in vitro and in human brain biopsy - Reuter, Martin; Kirsch, Peter (Social neuroscience, 2017)
The oxytocin system plays a prominent role in social behavior across species, and numerous genetic studies in humans have reported associations between polymorphisms on the oxytocin receptor (OXTR) gene and phenotypes related to social cognition, affiliation, perspective taking, and sociability in healthy subjects and in patients with atypical social behavior, such as in autism spectrum disorders (ASD). Recently, the first study demonstrating altered agonist-induced OXTR internalization and recycling for the exonic variant rs35062132 emerged. Beside this, there has been no further demonstration of the functionality of the OXTR variants especially there does not exist any for the regulatory units. To address this gap in the literature, we tested the functionality of the promoter flanking single nucleotide polymorphism (SNP) rs2268498, which has proven an interesting candidate for predicting social behavior in recent association studies. Results of genetic expression analyses in human hippocampal tissue showed a twofold difference in messenger RNA transcription, dependent on the presence or absence of the C-allele. This finding was corroborated by cloning, i.e., in vitro reporter gene expression analysis after transfection of OXTR promoter plasmids into HEK-293 cells. Our results underline the importance of OXTR rs2268498 for genetic research in social behavior and ASD.